Interest of Coffee Melanoidins as Sustainable Healthier Food Ingredients - Iriondo-DeHond, Amaia; Rodríguez Casas, Alejandra; del Castillo, Maria Dolores (Frontiers in Nutrition, 2021)
Coffee melanoidins are generated by the Maillard reaction during the thermal processes occurring in the journey of coffee from the plant to the cup (during drying and roasting). Melanoidins, the brown pigments formed as the end products of this reaction, have been reported in cascara, silverskin, spent coffee grounds and coffee brew. The latter is one of the main natural sources of melanoidins of the daily diet worldwide. However, their presence in coffee by-products has been recently described. These complex macromolecules possess multiple health promoting properties, such as antioxidant, anti-inflammatory, dietary fiber effect and prebiotic capacity, among others, which make them very interesting from a nutritional point of view. In addition, they have a great impact in the sensory profile of foods and their acceptance by the consumers. The present manuscript is a descriptive narrative mini-review about the nature, structure, digestibility, properties (sensory, nutritional and health promoting), safety and regulatory status of melanoidins from the coffee brew and its by-products with special emphasis on the latter.